2009
DOI: 10.1080/00365510802474400
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin as a biomarker of systemic inflammatory response in smoker patients with stable and exacerbation phases of chronic obstructive pulmonary disease

Abstract: Adiponectin may be a marker of low-grade systemic inflammatory response in COPD. A further rise in serum adiponectin in the exacerbation period denotes that this may also be a biomarker of the exacerbation phase as well as CRP and ESR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 32 publications
5
46
2
Order By: Relevance
“…37 In patients with COPD, the anti-inflammatory effect of adiponectin is more marked in severe and very severe stages as well as during exacerbations. 38,39 In our study, the serum adiponectin concentration was significantly higher in patients with frequent exacerbations, which seems to confirm its role in systemic inflammation. Thus, evaluation of serum adiponectin may be helpful in the identification of patients at higher risk of exacerbation.…”
supporting
confidence: 77%
“…37 In patients with COPD, the anti-inflammatory effect of adiponectin is more marked in severe and very severe stages as well as during exacerbations. 38,39 In our study, the serum adiponectin concentration was significantly higher in patients with frequent exacerbations, which seems to confirm its role in systemic inflammation. Thus, evaluation of serum adiponectin may be helpful in the identification of patients at higher risk of exacerbation.…”
supporting
confidence: 77%
“…Eker et al [19] found that in stable COPD patients leptin levels were low and the frequency of insulin resistance was high compared with the controls, although no difference in body FM was determined between the study populations. In other studies where COPD patients and controls were well matched for age, gender and BMI, the circulating leptin levels were not significantly different between stable COPD patients and healthy controls [17,24,25,30,31,32]. However, Gaki et al [33] demonstrated that leptin levels were higher in COPD patients who used inhaled corticosteroids.…”
Section: Resultsmentioning
confidence: 95%
“…In humans, down regulation of adiponectin and its receptors is associated with systemic inflammation and extrapulmonary effects, such as weight loss, osteoporosis, adipose atrophy, and skeletal muscle atrophy associated with age [6] . Recent human studies have demonstrated a significant increase in serum adiponectin levels in COPD and a direct correlation of these levels to the severity of the disease [7,8] . Plasma adiponectin is increased in underweight patients with COPD and is inversely associated with body mass index, degree of airflow limitation, and adverse cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%